2014
DOI: 10.14260/jemds/2014/3550
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Block Vertebrae in South Indians: An Osteometric Study

Abstract: BACKGROUND: Fusion of consecutive vertebral segments results in block vertebrae or vertebral synostosis or spinal fusion. The fusion may be complete or incomplete involving the bodies of the vertebrae alone or along with vertebral arch. It affects most commonly the cervical region, followed by thoracic and lumbar regions. AIM: The present study was aimed to assess the incidence of block vertebrae in south Indian population. METHODS AND MATERIAL: We examined a total of 2400 fully ossified dried vertebrae collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Fusion of vertebra at single or multiple levels is referred to as block vertebra or vertebral synostosis. 1 Cervical block vertebra are most commonly noticed followed by thoracic and lumbar spine. 3 The incidence of Spinal block vertebra has been shown to be 0.25% in South Asian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fusion of vertebra at single or multiple levels is referred to as block vertebra or vertebral synostosis. 1 Cervical block vertebra are most commonly noticed followed by thoracic and lumbar spine. 3 The incidence of Spinal block vertebra has been shown to be 0.25% in South Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal block vertebrae is a rare condition involving 0.25% of South Asian population. 1 In western world, 2.6%, 1.6% and 0.5% congenital fusions have been reported in cervical, thoracic and lumbar vertebra respectively. 2 As per a recent study, it has been shown that the thoracic and thoraco-lumbar spine is less affected by congenital fusion of the vertebral bodies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma et al studied 48 dried adult vertebral columns and noted CFCV in 6.25%, fused thoracic vertebrae in 4.16%, and fused lumbar vertebrae in 2.08% [5]. Nazeer et al examined 2,400 ossified dried vertebrae and encountered CFCV in 0.5%, fused thoracic vertebrae in 0.08%, and fused lumbar vertebrae in 0% [4], whereas, according to Deepa et al who studied 50 dry adult vertebral columns, the above-mentioned incidences were 2%, 4%, and 2%, respectively [21]. Ajay et al found CFCV incidence of 1.4% in the material of 280 dried adult cervical vertebrae [22].…”
Section: Discussionmentioning
confidence: 99%
“…The congenital fused cervical vertebrae (CFCV), which are usually two and, rarely, more than two in number, constitute a solitary unit that functions as one vertebra [3]. The incidence of CFCV varies between 0.5% [4] and 6.25% [5], whereas the frequency for the fused second and third cervical vertebrae (C2-C3) varies between 0.10% [6] and 1.33% [7]. CFCV usually are asymptomatic until adulthood, when degenerative changes, such as disc hernias and arthritis, are occurring above and below the CFCV’s level; in those cases, it is likely symptoms of nerve root compression will be noticed [8].…”
Section: Introductionmentioning
confidence: 99%